Rhizobial Inoculation Increases Soil Microbial Functioning and Gum Arabic Production of 13-Year-Old Senegalia senegal (L.) Britton, Trees in the North Part of Senegal - Fall, Dioumacor; Bakhoum, Niokhor; Nourou Sall, Saïdou; Zoubeirou, Alzouma Mayaki; Sylla, Samba N.; Diouf, Diegane (Frontiers in Plant Science, 2016)
Abstract Rhizobial inoculation has been widely used in controlled conditions as a substitute for chemical fertilizers to increase plants growth and productivity. However, very little is known about such effects on mature trees in natural habitats. In this study, we investigated the effect of rhizobial inoculation on soil total microbial biomass, mineral nitrogen content, potential CO2 respiration, fluorescein diacetate (FDA), acid phosphatase activities and gum arabic production by 13-years old Senegalia senegal (Syn. Acacia senegal) under natural conditions in the north part of Senegal during two consecutive years. Rhizobial inoculation was performed at the beginning of the rainy season (July) for both years with a cocktail of four strains (CIRADF 300, CIRADF 301, CIRADF 302 and CIRADF 303). Rhizospheric soils were collected in both dry and rainy seasons to a depth of 0-25 cm under uninoculated (UIN) and inoculated (IN) trees. Trees were tapped in November (beginning of dry season) using traditional tools. Gum arabic was harvested every 15 days from December to March. The results obtained from both years demonstrated that rhizobial inoculation increased significantly the percentage of trees producing gum arabic, gum arabic production per tree, soil microbial biomass, FDA and acid phosphatase activities. However, there was no significant effect on C mineralization and mineral nitrogen (N) content. Gum arabic production was positively correlated to rainfall, soil microbial biomass and mineral nitrogen content. Our results showed a positive effect of rhizobial inoculation on soil microbial functioning and gum arabic production by mature S. senegal trees. These important findings deserve to be conducted in several contrasting sites in order to improve gum arabic production and contribute to increase rural population incomes.